2015
DOI: 10.1007/s00428-015-1794-8
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation rate and breast cancer subtype, but not ALDH1 expression, predict pathological response to neoadjuvant chemotherapy in locally advanced breast cancer

Abstract: For locally advanced breast cancer, pathological complete response (pCR) following neoadjuvant chemotherapy (NACT) is associated with good disease-free survival. In several studies, response to chemotherapy according to various parameters has shown strong inter-individual variability. We investigated whether different prognostic factors, including ALDH1 expression, might predict response to NACT in female patients with locally advanced breast carcinoma. ER, PR, Her2/neu, Ki-67 and ALDH1 immunohistochemistry we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…24,25 Luminal breast cancer subtype had lower response to NAC when compare to other subtypes. 26,27 Although there were higher proportion of T4 breast cancer recruited in this current study, the rate of pCR in the current study was similar to the recent report of clinically node-positive breast cancer receiving NAC. 25 However, approximately 70% of the patients received neoadjuvant AC regimen which resulted in lower response when compare to the addition of taxane-based regimen.…”
Section: Discussionsupporting
confidence: 87%
“…24,25 Luminal breast cancer subtype had lower response to NAC when compare to other subtypes. 26,27 Although there were higher proportion of T4 breast cancer recruited in this current study, the rate of pCR in the current study was similar to the recent report of clinically node-positive breast cancer receiving NAC. 25 However, approximately 70% of the patients received neoadjuvant AC regimen which resulted in lower response when compare to the addition of taxane-based regimen.…”
Section: Discussionsupporting
confidence: 87%
“…This observation suggests that the presence of ALDH1-positive cancer stem cells correlates with early recurrence and shorter survival. Researchers in another study found patients with ALDH1-positive tumors to have poorer outcomes than those with ALDH1-negative tumors [ 6 , 20 , 26 , 28 – 31 ]. However, the authors of other reports noted no association of ALDH1 expression with poor outcomes [ 13 , 21 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1 can inactivate integral agents of NAC; therefore, breast cancer patients with high ALDH1 expression may have a low survival rate [ 20 ] and increased risk of recurrence. [ 10 ] Two other studies on all types of breast cancer also reported that the ALDH1 protein is a potential predictive marker of early local tumor recurrence and distant metastasis. [ 21 , 22 ]…”
Section: Discussionmentioning
confidence: 99%